BARRIERS ENCOUNTERED BY EFL STUDENTS IN LEARNING SYNTAX AT FIFTH SEMESTER IN ENGLISH DEPARTMENT OF SORONG MUHAMMADIYAH UNIVERSITY - Heriyanti Tahang (SELTICS, 2019)
This research aimed to describe kinds of barrier encountered by EFL students in learning Syntax at Fifth Semester in English Language Education Department of Universitas Muhammadiyah Sorong. This research used a qualitative method in the form of a descriptive qualitative design. 6 students as were as participants of this research. The participants were taken using purposive sampling through the criteria: students had difficulty in learning syntax. An interview was done to gather research data. Before conducting the research, Pre-Interview and Pre-Participation Observation in the Syntax Class to find out Students’ that have difficulties in learning Syntax were done. After that, the semi-structured interview used to know the barriers encountered by these students. Based on the data gained, the result of this research found that the students’ barrier in learning Syntax in English Language Education Department of Universitas Muhammadiyah Sorong were an emotional barrier, motivation barrier, and learning disability. From those of three barriers, most of the students tended to have fear, shame and emotional sensitivity as a most encountered barrier. Another barrier was motivation barrier such as Procrastination and Learning Environment, in addition to learning disability like depression, and dysgraphia. There are two kinds of Barrier that have not encountered by students, they are Lack of Prioritization and Dyslexia. Key words: Barriers, Learning Syntax